2014
DOI: 10.1177/0022034514544217
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of Posterior Composite Restorations

Abstract: The aim of this meta-analysis, based on individual participant data from several studies, was to investigate the influence of patient-, materials-, and tooth-related variables on the survival of posterior resin composite restorations. Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted a search resulting in 12 longitudinal studies of direct posterior resin composite restorations with at least 5 years' follow-up. Original datasets were still available, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
239
2
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(264 citation statements)
references
References 31 publications
6
239
2
17
Order By: Relevance
“…5 Restorative composites are not stable and continue to interact with the environment after polymerization. 16 Based on findings of the present study, composite resin aging influenced the bond strength of repair in an artificial saliva environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Restorative composites are not stable and continue to interact with the environment after polymerization. 16 Based on findings of the present study, composite resin aging influenced the bond strength of repair in an artificial saliva environment.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recent clinical studies and meta-analyses have established that repair is an alternative to replacement of defective restorations and increases the longevity of restorations with minimal intervention. 3,4,5 The total replacement of defective restorations may result in the loss of healthy dental structure and cause injury to the dentin-pulp complex. 6,7 The concept of repair instead of restoration is part of the philosophy of minimally Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have shown that composite restorations might have good clinical performance, with annual failure rates (AFRs) varying from 1% to 4%. 5,6,7,8,9 However, replacement of restorations is still very frequent in public and private practices, consuming a significant amount of clinical time and imposing high financial costs for health systems. At the end of the last century, it was estimated that £ 173 million of annual cost of England's national health care was only for replacing dental restorations.…”
Section: Introductionmentioning
confidence: 99%
“…10 Clinical studies evaluating the longevity of restorations usually aim to determine the risk factors and reasons for failures of restorations. Whilst the main reasons for failure in posterior restorations are dental caries and fractures of tooth and/or restoration, 9 in anterior teeth the esthetics factor play an important role in the choice of dentist and patient desire for new interventions. 6 In addition, the decision-making process on how to deal with a restoration with large or small defects can vary widely among dentists with different training status or background.…”
Section: Introductionmentioning
confidence: 99%
“…Foram avaliados então, 15 artigos na íntegra para elegibilidade, e desses, 4 foram excluídos com as seguintes razões: 1) Não apresentaram método explícito; 2) Resumo de uma revisão; e 3) Objetivo principal não era avaliar a longevidade das restaurações. Portanto, 11 artigos foram incluídos pela síntese qualitativa [8][9][10][11][12][13][14][15][16][17][18] e, desses, extraídos dados relevantes ao tema. A Tabela 1 mostra as características dos estudos incluídos e as comparações nas revisões.…”
Section: Resultsunclassified